Ri-posare Per un’ermeneutica dell’appartenenza in Merleau-Ponty, Dardel e Berque (Itinera, 2023)
What happens when consciousness fails? What happens to the connection with our experiences when we abandon ourselves to torpor, when “the light goes out”? Merleau- Ponty answered these questions in his course on Passivity, commenting on the status of the unconscious, sleep, dreams and memory. These are modalities through which the subject discovers a renewed adherence, a deeper sense of belonging to the world, and a peculiar ontological inherence or confidence. In the lethargic reabsorption, Merleau- Ponty so read Proust in The Problem of the Word, the sleeper rediscovers a carnal past with an enigmatic character, for which the anchorage to the stasis of rest, already personifies, the virtualities of a project, a specific “kinetic initiation”, the attribute of an ‘imminent movement’. It is from these intentions that one can trace the genesis of Dardel’s reflection on the nature of inhabiting, of human existence confined to the Earth. To inhabit a surface geographically is first and foremost to “rely, through sleep, on what lies (...) beneath us: the base on which our subjectivity folds”. To exist means “[re]starting from there (...) in order to untie from the surrounding world the ‘objects’ to which (...) our attention will be directed”. Starting from the Berquean assumption according to which the “spatiality of existence”, in all its meanings, “is movement and not -, conversely, motionless, and therefore sterile, - rootedness”, as also attested by Barbaras in L’appartenance, this essay highlights the essential character of ‘coexistence’ in which men and the world in its geographical consistency participate. It, therefore, investigates the conditions, the conjugations, as said, ‘terrestrial’, by means of which the ‘inner geography’ is articulated - and therefore, in the same way, disarticulated - as past, repetition and the creative newness, the future of which is the indispensable presupposition, is the ‘basis’; and the work of man, the implication of which ties his destiny to the ‘moving extension’ that is the Earth. This study concludes with the recognition of a twofold but unique, singular movement within existence, which alternates exhibition and withdrawal, vital élan and relapse into materiality, according to the coordinates of a “reality that is made through that which is undone”.
Keywords: Rest, Earth, Base, chora, médiance